2013
DOI: 10.1007/s11239-013-1014-9
|View full text |Cite
|
Sign up to set email alerts
|

Primary venous thromboembolism prophylaxis in patients with solid tumors: a meta-analysis

Abstract: Venous thromboembolism (VTE) is a leading cause of death among outpatient chemotherapy patients. However the VTE preventive measures for outpatients are not widely advocated. We did a meta-analysis to evaluate the outpatient VTE prevention's effectiveness and safety. We searched electronic databases until the end of December 2012 and reviewed the abstracts and manuscripts following the PRISMA guidelines. Occurrence of first VTE event was the efficacy outcome. The safety end point was major bleeding. We calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 45 publications
1
18
1
Order By: Relevance
“…The updated search identifi ed eight meta-analyses (1669-9861 patients) [103][104][105][106][107][108][109][110] and six randomised clinical trials [111][112][113][114][115][116] comparing anticoagulant prophylaxis with no intervention or placebo in ambulatory patients receiving systemic anticancer therapy. Overall, a signifi cant 45·0% reduction in VTE occurrence was reported across the six meta-analyses assessing the safety and effi cacy of LMWH compared with no intervention or placebo.…”
Section: Ambulatory Patients Treated With Systemic Anticancer Therapymentioning
confidence: 99%
See 3 more Smart Citations
“…The updated search identifi ed eight meta-analyses (1669-9861 patients) [103][104][105][106][107][108][109][110] and six randomised clinical trials [111][112][113][114][115][116] comparing anticoagulant prophylaxis with no intervention or placebo in ambulatory patients receiving systemic anticancer therapy. Overall, a signifi cant 45·0% reduction in VTE occurrence was reported across the six meta-analyses assessing the safety and effi cacy of LMWH compared with no intervention or placebo.…”
Section: Ambulatory Patients Treated With Systemic Anticancer Therapymentioning
confidence: 99%
“…Overall, a signifi cant 45·0% reduction in VTE occurrence was reported across the six meta-analyses assessing the safety and effi cacy of LMWH compared with no intervention or placebo. [103][104][105][106]108,109 Specifi c cancer subgroup analyses across the meta-analyses showed that LMWH significantly reduced the VTE prevalence compared with no treatment or placebo by 67·9-71·2% in patients with pancreatic cancer (range of 430-748 patients) and by 50·3-53·6% in patients with lung cancer (range of 1926-2075 patients). 103,105 Five of six meta-analyses reported no signifi cant increase in major bleeding with LMWH (13·0-30·0% of patients received LMWH and had major bleeding) compared with no prophylaxis.…”
Section: Ambulatory Patients Treated With Systemic Anticancer Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…
Our meta-analysis: ''Primary venous thromboembolism prophylaxis in patients with solid tumors'', was published on line in November 2013 [1]. We are writing to respond to comments made in a letter to the editor referencing our work.

The abstracted and analyzed information in our metaanalysis was obtained independently by 2 reviewers.

…”
mentioning
confidence: 99%